Testing Framework for IMS-Based IPTV - Tatiana Kovacikova; Pavol Segec (Communications - Scientific letters of the University of Zilina, 2012)
IPTV (Internet Protocol television) is one of the fast-growing communication services of the past years. Unfortunately, there is a lack of standardized deployed solutions and operators need to to rethink their position before upgrading IPTV solutions for next generation TV (HD TV and 3D TV). An efficient and up-to-date Interoperability Test Specification for IMS-Based IPTV is one of the opportunities for service providers and network operators to evaluate different features and services. TISPAN Release 3 covers many new use cases and features for IPTV (like user generated content, target advertising, etc.) and possible interactions with Voice/Data communications such as Social TV, Incoming Voice call management and notification on TV screen. In this paper, we will first provide a general overview of interoperability testing and its features. On an Instant Messaging use case, we will provide test descriptions including an end user test sequence as well as high level message flows at key standardized reference points in the TISPAN IMS-based IPTV infrastructure.